A matter of values: On the link between economic performance and Schwartz human values - Marcin Czupryna; Frederik Schaff (Journal of Economics and Statistics, 2024)
The goal of the paper is to propose an abstract but formalised model of how Schwartz higher order values may influence individual decisions on sharing an individual effort among alternative economic activities. Subsequently, individual decisions are aggregated into the total (collective) economic output, taking into account interactions between the agents. In particular, we explore the relationship between individual higher order values: Self-Enhancement, Self-Transcendence, Openness to Change and Conservation - measured according to Schwartz's universal human values theory - and individual and collective economic performance, by means of a theoretical agent based model. Furthermore, based on empirical observations, Openness to Change (measured by the population average in the case of collective output) is positively associated with individual and collective output. These relations are negative for Conservation. Self-Enhancement is positively associated with individual output but negatively with collective output. In case of Self-Transcendence, this effect is opposite. The model provides the potential explanations, in terms of individual and population differences in propensity for management, willingness to change and skills (measured by an educational level) for the empirically observed relations between Schwartz higher order values and individual and collective output. We directly calibrate the micro-level of the model using data from the ninth round of the European Social Survey (ESS9) and present the results of numerical simulations.
Keywords: E17; E27; 330; agent-based modelling; economic output; Schwartz values